Pentingnya Penggunaan Media Animasi dalam Meningkatkan Kemampuan Belajar Matematika Siswa Sekolah Dasar - Alfina; Ade Irmadurisa; Ana Rauhul Zannah; Aria Riski Ivansyah; Siti Istiningsih; Arif Widodo (Madako Elementary School, 2022)
The purpose of this study is to describe a literature review on the implementation of integrated learning in elementary schools. This study uses qualitative research methods with a library research process. Starting from collecting articles, regulating the number of articles, discussing, and concluding, this is the first step in collecting information in this research. Sources of articles or information obtained from previous research in the form of journal articles in the last 10-5 years (2012-2022). The study identified 8 out of 14 articles with similar topic titles. Several theories are helpful when applying blended learning in primary schools. The results show that the application of blended learning in elementary schools can increase student activity and learning outcomes at the elementary school level.